Research and Writing Development in the Area of Sport Science Publishing in Montenegro - Stevo Popovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
The purpose of this study is to analyses the personal scientifi c production of Montenegrin sports sciences researchers, as well as trend of publication within Montenegrin sports sciences journals. This investigation subject included the studies published in the period from 2002 to 2017 that have been focused on the sports sciences issues. The electronic databases (Google Scholar, Scopus and Web of Science) were searched for research articles available until 6 September 2018. Then research fi ndings were summarized in accordance with the PRISMA guidelines and the number of citation, h-index, i10-index as well as number of documents by authors were presented respectively. Results of this study indicated that the sports sciences researchers rapidly increased the number of publications from 2002 to 2017 and switch the writing language from Montenegrin to English, especially in last fi ve years. The number of citations span from 100 and 2800 within most of researchers, while h-index and i10-index span from 4 to 30 in most cases in Google Scholar database, while the same researchers were cited quite lesser in Scopus and Web of Science databases. On the other hand, in Google Scholar database, there are three registered Montenegrin journals: Sport Mont journal (over 1000 articles published since 2002) is the most cited one with highest h-index (16), Montenegrin Journal of Sports Science and Medicine (over 80 articles) is the best ranked Montenegrin journal, while Journal of Anthropology of Sport and Physical Education (over 40 articles) was established in 2017 and the relevant analyses could not be possible to be completed, while the analyses in Scopus and Web of Science were conducted for the Montenegrin Journal of Sports Science and it was reached quite lower score too. It was indicated the highest impact was recognized in the last years, regarding to citations of available articles published by Montenegrin authors, as well as writing style of articles published in English. Hence, the further deployment is expected in upcoming period.